Clinical features of Streptococcus intermedius infection in children: a case series study - Xu, Zhufei; Gao, Lichao; Xu, Dan; Yang, Dehua; Chen, Zhimin; Wang, Yingshuo (Frontiers in Microbiology, 2023)
Streptococcus intermedius is an opportunistic pathogen associated with prolonged hospital stays and high mortality rates in adults. However, little is currently known about the clinical features of Streptococcus intermedius infection in children. This retrospective case series study included 40 children diagnosed with Streptococcus intermedius, confirmed through bacterial cultures or high-throughput sequencing. Antibiotic resistance was assessed through susceptibility testing. The site and clinical manifestations were evaluated for all patients, revealing common infection sites such as the abdominal cavity, skin and soft tissue, intracranial, and invasive pulmonary, with the abdominal cavity being the most frequently affected. The drug susceptibility test showed 100% sensitivity to ceftriaxone, levofloxacin, chloramphenicol, vancomycin, and linezolid, 92.6% sensitivity to penicillin, 73.3% resistance to erythromycin, and 76.7% resistance to clindamycin. Besides antibiotic therapy, surgical intervention or pus drainage was often necessary. Lung imaging of four patients revealed pulmonary abscesses, nodules, or encapsulated pleura. Two cases yielded positive culture results, while three were identified as positive through high-throughput nucleotide sequencing of pleural effusion. In children with Streptococcus intermedius infection, emphasis should be placed on the risk of pus or abscess formation. In cases of pulmonary abscess and pleural effusion, especially in male children, Streptococcus intermedius should be suspected even if the culture is negative. Improvements in high-throughput nucleotide sequencing are required to reduce misdiagnosis rates.